Furin cleavage is required for swine acute diarrhea syndrome coronavirus spike protein-mediated cell – cell fusion. Issue 1 (31st December 2022) - Kim, Jinman; Yoon, Jaewon; Park, Jung-Eun
ABSTRACT: Swine acute diarrhea syndrome coronavirus (SADS-CoV) was reported in China in 2017 and is a causative agent of porcine enteric disease. Recent studies indicate that cells from various hosts are susceptible to SADS-CoV, suggesting the zoonotic potential of this virus. However, little is known about the mechanisms through which this virus enters cells. In this study, we investigated the role of furin in SADS-CoV spike (S)-mediated cell – cell fusion and entry. We found that the SADS-CoV S protein induced the fusion of various cells. Cell – cell fusion was inhibited by the proprotein convertase inhibitor dec-RVKR-cmk, and between cells transfected with mutant S proteins resistant to furin cleavage. These findings revealed that furin-induced cleavage of the SADS-CoV S protein is required for cell – cell fusion. Using mutagenesis analysis, we demonstrated that furin cleaves the SADS-CoV S protein near the S1/S2 cleavage site, 446 RYVR449 and 543 AVRR546 . We used pseudotyped viruses to determine whether furin-induced S cleavage is also required for viral entry. Pseudotyped viruses expressing S proteins with a mutated furin cleavage site could be transduced into target cells, indicating that furin-induced cleavage is not required for pseudotyped virus entry. Our data indicate that S cleavage is critical for SADS-CoV S-mediated cell – cell fusion and suggest that furin might be a host target for SADS-CoV antivirals.